SELF-EFFICACY KARIR DAN DUKUNGAN KELUARGA DENGAN ADAPTABILITAS KARIR SISWA SMA - Tarina Rahmaningtiyas; Wiwik Sulistiani; Dewi Mahastuti (Jurnal Psikologi Poseidon, 2021)
The current study examined the relationship between career self-efficacy and family support with with career adaptability indepedenly among students of SMAN 1 Pandaan. The number of respondents was 206 students of twelve grade SMAN 1 Pandaan, recruited through nonprobability sampling. The measuring instrument were CAAS (Career Adapt Adaptability Scale), Career Decision Making Self-Efficacy Scale (Indonesia Version) and family support scale from House and Khan. Data were analyzed using multiple correlation techniques. The results of the study show that there is a relationship between career self-efficacy and career adaptability of class XII students of SMAN 1 Pandaan, the direction of the relationship is positive. Other results show that there is no relationship between family support and career adaptability for class XII students of SMAN 1 Pandaan.